Effect of the fractionation of the nitrogen fertilization applied to the wheat crop on the quality of its seed - González-Figueroa, Sarahyt Santamaría; Aguirre-Mancilla, Cesar Leobardo; Covarrubias-Prieto, Jorge; Cervantes Ortiz, Francisco; Grageda-Cabrera, Oscar Arath (Revista Mexicana de Ciencias Agrícolas, 2018)
Seeds are an indispensable element in agricultural production and represent one of the means to improve crop yield and fertilization is essential for the production of high quality seeds. In the present work, the quality of the wheat seed was evaluated when the fertilizer-N is divided into different percentages. The varieties used were Gema C2004, Nana F2007 and Urbina S2007. The recommended N-P-K fertilization dose in the The Bajio region is 240-60-00. The fertilization-N divisions (FFN) were at planting, 45 days after sowing (dds) and 75 dds in the following percentages: 1) 00-00-00, 2) 100-00-00, 3) 00-100-00, 4) 50-50-00, 5) 00-50-50, 6) 70-30-00, 7) 30-70-00, 8) 00-30-70, 9) 00-70-30 and 10) 33-33-33. In the field the yield was evaluated, in the laboratory the physiological quality of the seed and in the greenhouse the vigor of the seedling in a sand bed. By fractionating the fertilizer-N at 30-70-00 and 33-33-33 the amount of m2 seeds increased, observing higher yields in wheat production compared to the recommended fertilization-N of 50-50-00 that currently used. The best emergency percentages were presented in the subdivisions 33-33-33, 30-70-00 and 70-30-00. Regarding vigor indexes IV-I and IV-II, the treatment that showed the highest values was 30-70-00. The FFN in which the best results were observed in the variables of yield, physiological seed quality and seedling vigor was 30-70-00.
Keywords: physiological quality; nitrogen; seedling vigor